Sastra arab sebagai jembatan: islamisasi di nusantara dan perkembangannya - Najma, Nur Afifah; Faradila, Najwa Riskiyah; Hasaniyah, Nur (Maliki Interdisciplinary Journal, 2025)
This research focuses on the role of Arabic literature in the process of spreading Islam in the Nusantara (Malay Archipelago) and its developmental journey through the analysis of various literary works, including religious texts, poetry, and hikayat (traditional tales). Arabic literature is more than a form of aesthetic expression; it also serves as a cultural bridge that unites Arab traditions with local cultures, as well as a tool in shaping the Islamic identity of the society. By using historical and textual analysis approaches, this article reveals how Arabic literary works contributed to disseminating Islamic values, strengthening religious thought, and shaping the cultural dynamics of Islam in the region. Moreover, this study explores how Arabic literature was locally adapted and its influence on the development of cultural, intellectual, and social aspects of the society. The findings indicate that Arabic literature functioned as an effective medium of da’wah (Islamic preaching) while enriching the Islamic literary tradition in the region. Thus, Arabic literature holds a significant role as both a cultural and intellectual bridge in the ongoing Islamization process.